The social behavior formation of master students in the process of their university studies - Makarova, Svetlana N.; Baulin, Alexey V. (The journal of contemporary issues in business and government, 2021)
The article contains results of the factors analysis that form a social behavior of master students in the learning process and during training period at a higher educational institution. In the research was distinguished: the degree of information of students about the purpose of magistracy, their motivation for studying in the magistracy, the tendency to implement research activities, and the financial situation of students. The object of research is the bachelor’s degrees’ students of a third and fourth years of study and master students of a first and second year of study from eight regional state universities of Russia. The article also provides comparative data with the results of studies implemented earlier, in 2011, 2014, and 2016 years, by the authors from eight Russian universities. The results of the study enable us to identify problems concerning certain aspects of the functioning of the institute of magistracy in the system of Russian higher education institutions.